COVID-19 preventive behavior among university students in Southeast Asia: Effects of knowledge, concern, awareness, and perceived risk - Al Mamun, Abdullah; Hayat, Naeem; Dieu, Huynh Thi My; Zainol, Noor R.; Salameh, Anas A. (Frontiers in Public Health, 2022)
The persistent rise of pandemics across the globe in recent times has led to the prescription of several collaborative preventive strategies to reduce the effect that the pandemic has on public health. Consistent monitoring and surveillance appear to be the only available approach to detecting and classifying the issues of public health threats. Global pandemic threats demand public co-operation to take preventive actions at a personal level so that the risk of infectious diseases can be contained. Said that, this study explored the influence of awareness of precaution measures (APM), concerns about Coronavirus Disease 2019 (COVID-19) (CAC), knowledge of COVID-19 (KOC), and perceived risk (PRK) on preventive behaviour (PRB), as well as the effect of age and gender on the relationships among the studied variables. Quantitative data was collected from 551 university students across Malaysia and Vietnam through field survey and online survey, respectively. The data collection was performed from March 13th to March 23rd, 2020. Partial Least Square Structural Equation Modelling (PLS-SEM) was employed for data analysis. The multiple group analysis (MGA) technique was applied to compare the data retrieved from the respondents based on age and gender. The results revealed that APM, CAC, KOC, and PRK on PRB significantly influenced PRB towards COVID-19. In light of the two personal factors; age and gender, significant variances were noted for age and KOC, while PRK on PRB on the PRB towards COVID-19. Based on the study outcomes, APM emerged as the most significant predictor of PRB, followed by PRK on PRB, and CAC. Since a large fraction of the world reside in rural areas and have high-level interaction with animals, the provision of education at all level can harness the attitude to adopt PRB towards COVID-19. As such, policymakers need to work with the young generation so that the latter may serve as change agents to spread the message of taking precautions and adopting effective PRB towards COVID-19.